Litterfall Pattern and Nutrient Dynamics of Swietenia macrophylla (King) Plantation In Terai Region, West Bengal, India - Dinesha, S.; Dey, A. N.; Vineeta; Deb, Shovik; Debnath, M. K. (Indian Forester, 2020)
The present study focuses the litter fall production, pattern and nutrient dynamics under Swietenia macrophylla plantation in Terai region of West Bengal, India. The total litter production was 6920.2 kg ha-1 yr-1 and 8387 kg ha-1 yr-1 in 2016-17 and 2017-18 respectively. The increase in annual total litter production in 2017-18 was 17% higher than the year 2016-17. It was observed that leaf litter showed higher nutrients than that of rachis litter. The leaf fraction had the highest amount of nutrient in the decreasing order of N > K > S > P whereas the same trend was followed in rachis litter. The nitrogen return of 92.98 kg ha-1 and 12.14 kg ha-1 was recorded in leaf and rachis, respectively whereas the return of phosphorous was 7.95 kg ha-1 and 1.08 kg ha-1. Similarly, the potassium nutrient return was 58.73 kg ha-1 and 8.30 kg ha-1 and the return of sulphur nutrient was 19.58 kg ha-1 and 1.38 kg ha-1 in leaf and rachis, respectively.